Pemanfaatan Serabut Kelapa dan Abu Ampas Tebu Sebagai Substitusi Fiberglass dan Semen Pada Pembuatan GRC Board - Alfitorh, Alfian Ma’arif (Jurnal Proyek Teknik Sipil, 2024)
In a construction project, the use of partition walls can cost quite a lot due to the high cost of raw materials used in partition walls. But unfortunately in the manufacture of GRC boards still use materials that are not environmentally friendly such as fiberglass (fiber fiber). Coconut fibers were used as additives because they have high tensile strength, while bagasse ash is used as a cement substitution to reduce production costs as well as help in reducing the amount of sugar industry waste. This study aims to find out the best mixture variations, density, water absorption,bending strength, hitting firmness, and price comparison. In this study, comparing conventional GRC Board with 3 variations of coconut fiber substitution mixture of 10%, 20%, 30% and bagasse ash 2.5%, 5%, 10% with a total of 48 samples and sizes for constancy tests at 20 cm x 20 cm x 0.6 cm and for flexural strength tests with a size of 10 cm x 10 cm x 0.6 cm. Mechanical testing based on SNI-01-4449-2006. The results of the test proved that the optimal mixture is in GRC Board D (30% coconut fiber and 2.5% bagasse ash) because it can produce better flexural strength and firmness than conventional GRC Board and GRC Board with bagasse ash and coconut fiber is 18% cheaper than conventional GRC Board.